A Research on the Creep Age Forming of 2524 Aluminum Alloy: Springback, Mechanical Properties, and Microstructures. (17th March 2014) - Zhan, Lihua; Tan, Sige; Yang, Youliang; Huang, Minghui; Shen, Wenqi; Zhao, Xing
Abstract : A series of orthogonal tests have been designed to investigate the combined effects of aging temperature, time, predeformation, and part thickness features on the springback of creep age forming of 2524 aluminum alloy sheets. Two springback prediction models containing the four process parameters mentioned above are developed based on experimental results and the multiple linear regression method. The comparisons of predicted and experimental values of springback yield good agreement. The dependence of springback on stress gradient across the thickness of sheet is examined in detail, showing that springback increases with the decrease in stress gradient while maintaining the ratio of bending radius to sheet thickness (R 0 / H ) as constant. In addition to springback, the mechanical properties and microstructural evolution are also researched. In the creep age forming process, the compression side of the sheet has higher mechanical properties and is characterized by more and finer precipitates in grains as compared to tension side.